Prophetic Paradigm as an Alternative Critique Toward Hart’s Concept of Morality and Law - Hamdani, Fitrah; Dimyati, Khudzaifah; Absori, Absori; Wardiono, Kelik; Dianto, Dianto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
"Prophetic Paradigm" generally refers to a framework or approach that emphasizes the role of prophecy or prophetic figures in shaping religious, spiritual, or social understanding. This paradigm is often discussed in religious contexts, particularly within Christianity, Islam, and Judaism, where prophets are seen as key messengers of divine will, providing guidance, correction, and insight to communities. This article critiques the ethical principles of the epistemological basis of the relationship between law and morality in Herbert Leonel Adolphus Hart's (H.L.A. Hart) rational paradigm, which is founded on the prophetic paradigm via the lens of the Medina Charter. It employs a philosophical approach to investigate the fundamental assumptions of the epistemological foundation of legal science by connecting legal science to prophetic science. This study's data are collected from literature. This analysis shows that Hart's proposed separation of law and morality is inappropriate. Some rules are both legal and moral. Thus, the criticism of morality in the Medina Charter demonstrates that the distinction between law and morality established by Hart cannot be generally implemented and must be evaluated by taking into account social context and moral ideals considered significant by the society.